Succession saisonnière et écophysiologie des diatomées arctiques : relation entre l'habitat, la niche lumineuse et la stratégie photoadaptative - Croteau, Dany (Université Laval, 2019)
Over their highly productive seasonal succession, Arctic diatoms occupy shifting habitats and contrasted light climates defined by snow/ice cover dynamics and extreme photoperiod variations. These unique light environment features suggest Arctic diatoms are well adapted to survive prolonged darkness periods, exploit minimal light in snow-covered sea-ice and overcome spontaneous excessive, and potentially harmful, light exposures. Diatoms mitigate photooxidative damages by dissipating oversaturating light energy as heat via the non-photochemical quenching (NPQ), mainly regulated by the xanthophyll cycle (XC). How heterogeneous light niches influence Arctic diatoms photoadaptative traits remains largely unknown and a crucial missing link to apprehend Arctic Ocean’s response to shrinking sea-ice and increasing illumination. To address this question, we selected five Arctic diatoms species harbouring diverse life traits and representative of distinct phases across the seasonal light niche continuum: from snow-covered dimly lit bottom sea-ice to summer stratified waters. To access how Arctic diatoms cope with a heterogeneous light environment, we studied their acclimation to two light intensities and subsequent darkness incubations, and parametrized NPQ-XC induction upon light shifts. Our results highlight the sea-ice cover as a strong selective force shaping Arctic diatoms photoadaptative strategies. Ice-related species exhibited a survivalist photoadaptive strategy with growth saturating at low irradiance and strong photoprotective capabilities sustained even in darkness. Open-water species photophysiology was more dynamic, expressing flexible light utilisation capacities and great photoprotection capacities triggered by high light and darkness. Ice-edge species showed strong adaptation to light fluctuations and dark physiology fine-tuned depending upon light history. We argue that diverging photoadaptative strategies foster Arctic diatom success in their respective seasonal niches and will likely drive uneven ...